Frequency and Clinical Characteristics of Young Onset Parkinson’s Disease at Chandka Medical College Hospital Larkana - Nagina Shaikh, Abu Bakar Shaikh, Suhail Ahmed Aghani, Sameena Majeed, Irfana Abbasi, Muhammad Munwar Ali, Alam Ibrahim Siddiqui, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the most prevalent forms of neurodegenerative illness, Parkinson's is characterised by a loss of postural response, stiffness, and tremor at rest. Young-onset Parkinson's disease occurs between the ages of 21 and 50 on average, however it begins much younger in 3 to 5 percent of people. Objective: To determine frequency of Young onset Parkinson’s disease in Parkinson’s patients. Methodology: This research was conducted from May 2022 and October 2022 at the Chandka Medical College Hospital in Larkana. The World Health Organization's online calculator determined that 73 people would be used for the study. Permission and ethical review forms were filled out. The data was analysed using SPSS. The significance level of 0.05 was considered crucial. Results: The total number of female patients were 31(42.5%) while male were 42(57.5%) The duration of disease was from 6 months to 22 years. Majority of the patients were in stage 2 and 3 according to Hoehn and Yahr rating scale. The frequency of Young Onset Parkinson’s disease in Parkinson’s patients is 24.7%. Overall prevalence of Parkinson’s disease was seen more in male patients, this even increases in YOPD, (38% VS 62%).Almost all patients in both age categories have bradykinesia and rigidity while 6 patients out of 73 have absent tremors. Loss of postural reflex was seen in 33 patients, every second (51%) patient in idiopathic Parkinson’s disease and every third (38%) in YOPD. Dystonia was seen more in YOPD, total 8 patients have dystonia, 4(28%) in YOPD and 4(8%) in Idiopathic Parkinson’s disease. Dyskinesia was not seen in YOPD while it was frequent in Idiopathic Parkinson’s disease. Family history was positive in total 9 patients, 50% of cases YOPD, while it was positive 5.8% in idiopathic Parkinson’s disease. Conclusion: YOPD is unique subgroup among patients of Parkinson’s disease, it burden is much more than ever reported, this calls for shared decision making , the possibility of genetic counseling and appropriate multidisciplinary treatment options. Keywords: Parkinson’s disease, YOPD (Young onset Parkinson’s disease, bradykinesia, rigidity, tremor, dystonia, postural reflex. Dyskinesia.